Dead line [large type] - Cameron, Marc (Cameron, Marc. Arliss Cutter novel, 2025)
"In the White Mountain Wilderness of Interior Alaska, twenty-four-year-old protected witness Sam Lujan is lonely for his old life. So much so, the young Apache not only breaks the cardinal rule of the Witness Protection Program-by revealing his whereabouts to his mother-he invites her to join him to see the Northern Lights. It's her lifelong dream. When Deputy U.S. Marshals Arliss Cutter and Lola Teariki discover Sam has gone missing, they're asked to make a quick trip into the remote wild to make sure the witness is indeed protected. Now they're plunging headlong into the frozen unknown at fifty-eight degrees below zero. Valeria Kot, the vengeful daughter of the criminal Sam testified against, has been waiting and watching for years for just the opportunity to strike back. She's found it-and has dispatched a sadistic hit squad to make sure Sam pays in the most savage way possible. Once Arliss and Lola reach the trailhead it doesn't take long for them to realize they're dealing with more than a witness who's broken protocol. For Arliss and Lola, and a desperate mother and son on the run, the death-defying, frigid temperatures are the least of their worries."--